2009
DOI: 10.1111/j.1524-475x.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of bone marrow‐derived mesenchymal stem cells induced by tumor necrosis factor‐α and its possible role in wound healing

Abstract: We aimed to investigate the effect of tumor necrosis factor-alpha (TNF-alpha) on the expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in the migration ability of mesenchymal stem cells (MSCs) in the context of wound healing. We also explored the role of p38 mitogen-activated protein kinase and extracellular signal-regulated kinase (ERK) signaling pathways in the migration of MSCs. MSCs were isolated from the bone marrow and cultured. Immunocytochemistry, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 38 publications
3
78
1
Order By: Relevance
“…It has been shown that ICAM1 plays an important role in direct cell-to-cell contact-mediated signals via mitogen-activated protein kinase (MAPK) pathway including p38, extracellular signal-regulated kinase (ERK) 1/2 and c-Jun N-terminal kinase (JNK) 1/2/3 (Cernuda-Morollon and Ridley 2006, Turowski et al 2005), which could subsequently stimulate osteoblast differentiation of stem/progenitor cells. Fu et al (2009) further suggested that ICAM1 and p38 MAPK also significantly influence the migration of stem cells to their target sites, such as PDL tissue and alveolar bone. These previous evidence, together with our present results, suggest that ICAM1 could also play a significant part in signals initiated by direct cell-to-cell and cell-to-matrix contact, thus subsequently enhancing osteoblast differentiaon of stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ICAM1 plays an important role in direct cell-to-cell contact-mediated signals via mitogen-activated protein kinase (MAPK) pathway including p38, extracellular signal-regulated kinase (ERK) 1/2 and c-Jun N-terminal kinase (JNK) 1/2/3 (Cernuda-Morollon and Ridley 2006, Turowski et al 2005), which could subsequently stimulate osteoblast differentiation of stem/progenitor cells. Fu et al (2009) further suggested that ICAM1 and p38 MAPK also significantly influence the migration of stem cells to their target sites, such as PDL tissue and alveolar bone. These previous evidence, together with our present results, suggest that ICAM1 could also play a significant part in signals initiated by direct cell-to-cell and cell-to-matrix contact, thus subsequently enhancing osteoblast differentiaon of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM1 is an important cell surface adhesion molecule found in many cell types including in stem/progenitor cells and osteoblasts (Fu et al 2009, Tanaka et al 1995. Several lines of evidence support that ICAM1-mediated direct cell contact has a major impact on a wide range of biological responses including cell differentiation (Gortz et al 2004, Long et al 1995, Olsen et al 1988, Saho et al 2003, Tanaka et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening the adhesion of MSCs to T cells via ICAM-1 proportionally potentiates the function of MSCs represented by lagging of T cells proliferation [204] . Besides the direct role of ICAM-1 in MSCs interaction with immune cells, the importance of membrane expression of ICAM-1 spans MSCs migration [208] , proliferation and differentiation capacity [209] . Seemingly indirectly related, the essence of the processes like migration, proliferation and differentiation of MSCs is also regulated by the inflammatory environment [66] .…”
Section: Intercellular Adhesion Moleculementioning
confidence: 99%
“…Utilising a TNFa antagonist in a rat growth plate injury model, Zhou et al (2006) found that blocking TNFa resulted in a clear delay in the subsequent mesenchymal infiltration response and a reduction of the proliferation of these cells . Similarly, separate studies looking at the role of TNFa during bone fracture repair and wound repair have also found that its inhibition leads to a significant delay in overall mesenchymal progenitor or stem cell (MSC) infiltration and subsequent healing (Gerstenfeld et al 2001, Fu et al 2009). More studies have reported the importance of TNFa in regulating recruitment of MSC, their proliferation and differentiation (Barnes et al 1999, Martin et al 2003, Dimitriou et al 2005.…”
Section: The Inflammatory Phasementioning
confidence: 99%